Model-based design of a novel modular mounting system: Light, compact, and efficient. (September 2022) - Qiu, Yuanran; Xu, Wei; Hu, Zechao; Zhang, Shengwu
Two-stage mounting systems applied in ships are expected to be light in weight, compact in installation space, and efficient in vibration isolation performance at the same time, which largely increases the engineering complexity. In this paper, analytical models of a two-stage mounting system with flexible and rigid intermediate mass are proposed to compare the vibration isolation effectiveness (VIE) performance and the influences of system parameters with the rigid intermediate mass on VIE are introduced. Based on the analysis results, an integrated adjustable two-stage mounting module is designed. Compared to the traditional floating raft mounting system with flexible intermediate mass, this two-stage mounting module can be arranged in a more compact structure space with greatly reduced size and weight. Furthermore, a novel modular mounting system prototype is proposed and manufactured based on several two-stage mounting modules and real-time behavior monitoring and controlling subsystem. The testing results verify the compatibility of the module design and the behavior monitoring and controlling system. The modular mounting system also exhibits excellent VIE performance combined with the advantage of compact intermediate mass size, lightweight, and automatic behavior monitoring and controlling.